2024
DOI: 10.1021/acsnano.3c09491
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Viro-chemoimmunotherapy in Breast Cancer Enabled by Bioengineered Immunostimulatory Exosomes and Dual-Targeted Coxsackievirus B3

Amirhossein Bahreyni,
Yasir Mohamud,
Sanaz Ashraf Nouhegar
et al.

Abstract: Breast cancer's immunosuppressive environment hinders effective immunotherapy, but oncolytic viruses hold promise for addressing this challenge by targeting tumor cells and altering the microenvironment. Yet, neutralizing antibodies and immune clearance impede their clinical utility. This study explored microRNA-modified coxsackievirus B3 (miR-CVB3), an innovative oncolytic virus, and its potential in breast cancer treatment. It investigated miR-CVB3's impact on immune-related proteins and utilized exosomes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The final therapeutic platform ExomiR-CVB3/DoxApt demonstrated improved targeting and cytotoxic capabilities against subcutaneous breast cancer in mice after intraperitoneal injection. 72 In addition to using naturally secreted cell particles, some studies have reported the generation of artificial enveloped viruses by co-extruding OAs with cancer cell membranes. This method not only preserved the virus’s activity, but also enhanced its anti-tumor capabilities after intratumoral injection.…”
Section: Cell Membrane-derived Nanovesiclesmentioning
confidence: 99%
“…The final therapeutic platform ExomiR-CVB3/DoxApt demonstrated improved targeting and cytotoxic capabilities against subcutaneous breast cancer in mice after intraperitoneal injection. 72 In addition to using naturally secreted cell particles, some studies have reported the generation of artificial enveloped viruses by co-extruding OAs with cancer cell membranes. This method not only preserved the virus’s activity, but also enhanced its anti-tumor capabilities after intratumoral injection.…”
Section: Cell Membrane-derived Nanovesiclesmentioning
confidence: 99%
“…Cancer immunotherapy has become a viable therapeutic option for the treatment of various cancers. , However, the immunosuppressive tumor microenvironment (TME) limits the efficacy of current immunotherapeutic strategies . Oncolytic viruses (OVs) have gained significant attention in cancer therapy due to their strong ability to induce immunogenic cell death (ICD). , It has been shown that OVs can drive antitumor immunity and alleviate the immunosuppressive TME by releasing tumor-associated antigens (TAAs) to recruit T cells to the immune-excluded or immune-abandoned TME. OVs have also shown promise in improving the efficacy of immune checkpoint blockade (ICB) therapies. , Despite the encouraging potential of OVs and the fact that various OVs are under clinical investigation, OVs monotherapy or combination with immune checkpoint inhibitors (ICIs) have not achieved satisfactory clinical results. Therefore, exploring the mechanisms underlying the poor outcome of OVs therapy and optimizing OVs therapeutic strategies has become a top priority.…”
Section: Introductionmentioning
confidence: 99%